Perancangan Sistem Informasi Wedding Organizer Berbasis Android - Bernadetha, Sri Melati; Silitonga, Parasian D.P (UNIKA Santo Thomas, 2022)
Wedding Organizer is a team of wedding coordinators who work together to assist the implementation of wedding events whose job is to arrange the course of the event starting from the aisle, catering, bridal makeup, to documentation. The purpose of this research is to design an android-based wedding organizer application to make it easier for brides and grooms to order wedding packages via android devices. The research method used is the waterfall model SDLC method which has 5 stages including Requirement, Design, Implementation, Verification, Maintenance. The benefit of this research is an application designed to provide convenience between each party wedding organizer and the bride and groom in supporting the needs of wedding events with android application media, so that the service process will be more effective and efficient. The results obtained are in the form of a wedding organizer application that can be run on smartphone media with the Android operating system that has gone through the testing phase